ePortfolio implementation strategy of FH JOANNEUM - Hiller, Bettina; Pauschenwein, Jutta; Sandtner, Heimo; Sfiri, Anastasia; Porotschnig, Barbara; Ritter, Gabriella (International Journal of Emerging Technologies in Learning (iJET), 2008)
This paper describes the design of Portfolio and its application at FH JOANNEUM in a range of contexts where it will be used to make learning outcomes visible and to facilitate personal development planning. The flexibility of the ePortfolio architecture is appraised and the integration with virtual learning environments is discussed. Preliminary findings from evaluation studies (feedback / data obtained from students, graduates and staff evaluations and discussions, and relevant points arising from the round table experts´ discussion, Jan. 07) are summarised. Aspects of validity, reliability and manageability for the implementation of portfolios are deduced.